And they will even believe that in this way they worship God (Jn 16: 2) - Flores Lizana, Carlos (2003)
The title of this work has been carefully chosen, because there are people who in the name of God have killed human beings, most of them Christians, poor peasants, children, young people, women... And tragically, as Jesus himself announced Just before being assassinated by the religious authorities of their time, they believed they were doing good and even serving the God of Jesus. I had that experience in front of people who believed they were serving God and killed their brothers, some directly and others allowing this to happen, that is, being complicit in silence or indirectly collaborating with an anti-subversive struggle that has produced the majority of the disappeared detainees of the last 20 years. This article is part of a more extensive and documented text that I am preparing as a contribution to the tasks of the Truth and Reconciliation Commission.